Working toward anti-racist perspectives in attachment theory, research, and practice - Stern, Jessica A.; Barbarin, Oscar; Cassidy, Jude (Attachment & human development, 2022)
Recent social movements have illuminated systemic inequities in U.S. society, including within the social sciences. Thus, it is essential that attachment researchers and practitioners engage in reflection and action to work toward anti-racist perspectives in the field. Our aims in this paper are (1) to share the generative conversations and debates that arose in preparing the Special Issue of Attachment & Human Development, "Attachment Perspectives on Race, Prejudice, and Anti-Racism"; and (2) to propose key considerations for working toward anti-racist perspectives in the field of attachment. We provide recommendations for enriching attachment theory (e.g. considering relations between caregivers' racial-ethnic socialization and secure base provision), research (e.g. increasing the representation of African American researchers and participants), and practice (e.g. advocating for policies that reduce systemic inequities in family supports). Finally, we suggest two relevant models integrating attachment theory with perspectives from Black youth development as guides for future research.